Utilization of Melt Solidification Technique in the Development of Sustained Release Pastilles of BCS Class –III Anti-diabetic Drug - Ahire, Sandip Barku (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: Basically, this research work focused to explore the use of solid lipid as alternative to polymers and solvent free process for formulation of sustained release dosage form such as pastilles by making laboratory scale fabricated melt solidification apparatus. Materials and Methods: Melt solidification technique was used for the formulation of sustained release pastilles of metformin hydrochloride. For the optimization response surface methodology Box–Behnken design were implemented. Results: The lab scale fabricated device was evaluated at 20G size of needle and cooling plate temperature at 4°C.The formulated pastilles was characterized for their size and shape, crushing strength, flow properties, contact angle, % friability, % drug content uniformity, and thermal properties by differential scanning calorimetrty, evaluation of pore formation done by scanning electron microscopic study. The in vitro dissolution study revealed sustained release through lipid matrix up to 8–10 h. More than 95% drug released was observed at 10 h. The formulated Pastilles were somewhat spherical in shape and size in the range 2.5–3.5 mm; however, the angle of contact of pastilles was found to be more than 115°. Pore former quantity plays key role, it was enhanced the dissolution rate. Conclusion: Pastillation technique is very effective technique for the formulation of pastilles with desired size, shape, crushing strength, contact angle, and with sustained release of drug.